Revisiting polymer crystallization kinetics: experimental validation of the Mo equation for modified PET systems - Lingcong, Ma; Fengyu, Mao; Yajuan, Wu; Ying, Peng; Fei, Luo; Jin, Wen (Frontiers in Materials, 2025)
This study investigated the non—isothermal crystallization kinetics of pure poly(ethylene terephthalate) (PET) and chain—extended modified PET using DSC at various cooling rates. Through comparing Avrami, Ozawa, and Mo methods, the Mo method was found most effective in describing non—isothermal crystallization. The kinetic parameter F(T) indicated that pure PET crystallized faster than modified PET due to reduced chain mobility in the latter. A positive correlation between F(T) and relative crystallinity was established, showing higher cooling rates accelerate crystallinity development. The E44—modified PET had minimal impact on crystallization kinetics, making E44 a promising modifier. These findings advance the understanding of PET crystallization, and the Mo method serves as a robust framework for related studies, promoting polymer kinetics and opening new avenues for material innovation.